Análise espacial das variações das Taxas Específicas de Fecundidade de 15 a 19 anos e do Índice de Desenvolvimento Humano entre 2000 e 2010 nas microrregiões do Brasil - Paulo Henrique Viegas Martins (2020)
The age specific fertility rates from 15 to 19 years old have always been at very high values since the beginning of the Brazilian demographic transition until the 2000s. At the beginning of this century, there was an important reduction in fertility in this age group. The explanations for these changes are diverse and, more recently, have been based on structural factors. In this sense, one of the factors highlighted by the literature on this topic are the important advances in the levels of development, mainly in some locations in Brazil. Although some studies suggest that this change in adolescent fertility rates is related to advances in levels of development, few, in fact, evaluate this relationship. In order to seek explanations for these trends in adolescent fertility, the main objective of this thesis is to evaluate and discuss the relationship between adolescent fertility and development in Brazilian micro-regions between 2000 and 2010. Although several indicators can be used to represent levels of development of the localities, in this study we used the Human Development Index (HDI), because it is a measure that seeks to reflect the behavior of education, income and health of the populations. In this sense, the first specific objective of this thesis was to analyze the spatial patterns of variation in the specific fertility rates of adolescents and the HDI in the Brazilian micro-regions between 2000 and 2010. The second specific objective of the study was to analyze the spatial distribution of the association between variations in adolescent fertility rates and HDI between 2000 and 2010 in Brazilian micro-regions. To achieve this result, two methodological procedures were used. First, we checked whether the variations in the fertility rates of adolescents and the HDI showed a spatial pattern. Then, we examine the spatial distribution of the association between variations in adolescent fertility rates and the HDI in Brazilian micro-regions. We used the information from the 2000 and 2010 Demographic Census to estimate fertility rates between 15 and 19 years old. To estimate the HDI of the 557 microregions, we used a weighted average of the municipal HDI, with weights given by the size of each of the municipalities that comprise it. The results of the first analysis demonstrate that there is indeed a spatial pattern of variation in adolescent fertility and the HDI, which suggests that the characteristics of the space are influencing the variations in these two variables. The results of the second analysis demonstrate that the relationship between the variations in these two variables occurs only in a few locations in the country, suggesting that, despite the important role of development for the decline in adolescent fertility rates, there are other variables that are influencing this behavior, as also presented in the literature. In view of the results we found in this thesis, the importance of the spatial context for the decline in adolescent fertility rates was noted. It is also observed that the role of the HDI in reducing fertility rates is small and that, probably, other variables may have a greater influence on these rates. This study contributed to the understanding of spatial and temporal variations in adolescent fertility rates, in addition to investigating the role of levels of development, measured by the HDI, in these variations.